2022
DOI: 10.1186/s12886-022-02530-8
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal and retinal thickness in patients with vitamin C deficiency using swept-source optical coherence tomography

Abstract: Background To investigate the effects of vitamin C on central retinal thickness and choroidal thickness. Methods A total of 69 patients diagnosed with vitamin C deficiency and 1:1 age- and gender-matched 69 healthy individuals with normal serum vitamin C were included in this study. Demographic characteristics of the individuals were collected. All patients underwent a comprehensive ophthalmic examination. Subfoveal choroidal thickness and retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The pathophysiology of the glaucomas includes retinal ganglion cell apoptosis and an increased photopic negative response. Quercetin has shown a photopic negative response, an index of glaucomatous damage in murine models, proving it to be a viable anti-glaucoma supplement [ 361 ]. Quercetin has also been shown to reduce apoptotic cell death, thereby protecting retinal ganglion cells in rat models [ 362 , 363 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pathophysiology of the glaucomas includes retinal ganglion cell apoptosis and an increased photopic negative response. Quercetin has shown a photopic negative response, an index of glaucomatous damage in murine models, proving it to be a viable anti-glaucoma supplement [ 361 ]. Quercetin has also been shown to reduce apoptotic cell death, thereby protecting retinal ganglion cells in rat models [ 362 , 363 ].…”
Section: Resultsmentioning
confidence: 99%
“…Decreases in vitamin C levels correlate with the severity of macular ischemia [96]. Qian et al found that central retinal and choroidal thickness is reduced in patients with a vitamin C deficiency [97].…”
Section: Vitamin Cmentioning
confidence: 99%